2020
DOI: 10.1177/2150132720924432
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Comprehensiveness and Care Coordination in Robust Specialist Networks Results in Lower Emergency Department Utilization: A Network Analysis of Medicaid Physician Networks

Abstract: Background: Care coordination is an essential and difficult to measure function of primary care. Objective: Our objective was to assess the impact of network characteristics in primary/specialty physician networks on emergency department (ED) visits for patients with chronic ambulatory care sensitive conditions (ACSCs). Subjects and Measures: This cross-sectional social network analysis of primary care and specialty physicians caring for adult Medicaid beneficiaries with ACSCs was conducted using 2009 Texas Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
5
0
2
Order By: Relevance
“…43,44 Independent of race/ethnicity and insurance, we found that patients who did not have a PCP had a higher relative risk of seeking testing at the ED, UC, and MTU sites compared with OP care, consistent with prior literature that having a PCP is associated with decreased ED utilization. 45,46 In the summer of 2020, Atrium Health was able to operationalize the benefit of having an established PCP to reach patients in community clinics and provided them information on how to use OP care for testing. 37 However, similar to published literature, in our study, a lower percentage of Black and Hispanic patients had a PCP compared with White patients.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 Independent of race/ethnicity and insurance, we found that patients who did not have a PCP had a higher relative risk of seeking testing at the ED, UC, and MTU sites compared with OP care, consistent with prior literature that having a PCP is associated with decreased ED utilization. 45,46 In the summer of 2020, Atrium Health was able to operationalize the benefit of having an established PCP to reach patients in community clinics and provided them information on how to use OP care for testing. 37 However, similar to published literature, in our study, a lower percentage of Black and Hispanic patients had a PCP compared with White patients.…”
Section: Discussionmentioning
confidence: 99%
“…Diante de um sistema fragmentado, a população acaba por se "acomodar" ao atendimento de especialistas focais 15 . Estudos ratificam que provedores de APS que atuam em redes nas quais exercem baixo grau de centralidade, mesmo com disponibilidade de especialistas, não diminuem a utilização de serviços de emergência de seus pacientes com agravos crônicos, ao contrário daqueles que exercem alto grau de coordenação e cuidados abrangentes 2 .…”
Section: Dimensões E Componentesunclassified
“…As barreiras aos cuidados especializados são generalizadas e multifatoriais, com consequências no acesso oportuno, resultados e equidade em saúde, em contextos urbano e rural 1,2 . O "valor" dos sistemas de saúde envolve, entre outros aspectos, melhoria da qualidade, redução das hospitalizações, exames e procedimentos desnecessários a partir do reposicionamento da atenção especializada (AE), na interface com os serviços de Atenção Primária à Saúde (APS) 3 .…”
Section: Introductionunclassified
“…In a fragmented system, the population "grows accustomed" to treatment by specialists 15 . Studies show that PHC providers in networks who have a low degree of centrality, even with the availability of specialists, do not reduce the utilization of emergency services by their patients with chronic conditions, in contrast to those who had a high degree of care coordination and a robust specialist network available 2 .…”
Section: Dimensions and Componentsmentioning
confidence: 99%
“…Barriers to specialized care (SC) are general and multifactorial, with consequences for timely care, outcomes, and health equity in both urban and rural settings 1,2 . Increasing the "value" of health systems entails, among other things, improving quality and reducing unnecessary hospitalizations, tests, and procedures by repositioning SC and creating an interface between SC and primary health care (PHC) services 3 .…”
Section: Introductionmentioning
confidence: 99%